RESULTS OF TREATMENT OF CLOSED PROXIMAL HUMERUS FRACTURES USING LOCKING PLATES (Vietnam Journal of Community Medicine, 2026)
Objectives: Evaluate the results of treatment of closed proximal humerus fractures using locking plate at 108 Central Military Hospital. Subjects and Methods: A descriptive study of 51 patients who underwent open reduction and internal fixation with PHILOS plate between January 2024 and OctoberThere were 19 men and 32 women with a mean age of 61 years. There were 31 patients in the age group of > 60 years. Results: Neer classification by fracture group: Group III accounted for 21.6%, Group IV for 50.9%, Group V for 11.7% and Group VI for 15.7%. Functional evaluation of the shoulder at final follow-up was done using Neer Shoulder Score. The mean follow-up period was 14 months. The results were good in 32 patients (62.7%), fair in 19 patients (37.3%), and no cases had average or poor results. During the follow-up, no cases of infection, avascular necrosis or nonunion were noted.Conclusion: Locking plate fixation for closed proximal humerus fractures provides stable fixation, high union rates, and satisfactory functional outcomes. This method allows early mobilization and is effective even in complex fractures or osteoporotic bone.
Keywords: Proximal humeral fractures, locking plates.